Peningkatan Kapasitas dan Membangun Branding BUMDes Tigalunggung, Desa Linggajati, Kabupaten Tasikmalaya - Nuraini, Candra; Atmaja, Unang; Rosliyati, Ati; Mutolib, Abdul (Research and Social Study Institute (RESSI), 2024)
This community service activity aims to increase capacity and build palm sugar branding. Community service activities are carried out from August to October 2021. The target of this service is the management of the BUMDes Tigalunggung, Linggajati Village, which consists of 10 people. Community service activities are carried out through the lecture method on BUMDes management materials, Financial Management, and Building Branding for BUMDes Tigalunggung palm Sugar Products. Service activities consist of three stages, namely the preparation stage, service activities, and comparative studies (field studies). The main problem faced by BUMDes Tigalunggung is the low capacity of BUMDes managing human resources. BUMDes management and finance training is an effort to increase the capacity of Tigalunggung BUMDes managers. The training participants were enthusiastic in participating in the training as an effort to build the independence of BUMDes. Some of the weaknesses of BUMDes Tigalunggung sugar products include product processing that is not standardized, drying is still traditional and relies on the sun, does not have a P-IRT permit, does not have a halal guarantee certificate (SJH), product packaging that is not informative in terms of design and nutritional value information, and the limited marketing network for palm sugar products. Improving the quality of palm sugar products BUMDes Tigalunggung is expected to improve the quality of product branding and attract consumers to buy palm sugar products belonging to BUMDes Tigalunggung.